ANALISIS PENGARUH KARAKTERISTIK BANK DAN INFLASI TERHADAP NET INTEREST MARGIN Studi Kasus Pada Bank Konvensional yang Terdaftar di Bursa Efek Indonesia Tahun 2006-2010 - Hidayat, Taufik; Hamidah, Hamidah; Mardiyati, Umi (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2012)
This paper investigates the influence of bank’s characteristics and inflation on commercial bank’s interest margins in Indonesia for the 2006-2010 period. The empirical results suggest that bank-specific characteristics, in particular bank capitalization and efficiency have a positive and significant impact on bank’s net interest margins. The bank size and liquidity have a negative and significant impact on bank’s net interest margins. We also find that inflation has a negative and significant impact on net interest margin (at level 10%). Key words : bank interest margin, panel data, Indonesia.